2005
DOI: 10.1097/01.blo.0000185450.89364.10
|View full text |Cite
|
Sign up to set email alerts
|

Minimal-Incision Total Knee Arthroplasty

Abstract: Prognostic study, Level III-1 (retrospective cohort study). See the Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
77
0
8

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(90 citation statements)
references
References 12 publications
5
77
0
8
Order By: Relevance
“…There are well-established and proven advantages such as less blood loss, less postoperative pain, smaller scar and faster recovery of knee function [4,7,10,12,13]. However, all these advantages apply only to the early period after TKR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are well-established and proven advantages such as less blood loss, less postoperative pain, smaller scar and faster recovery of knee function [4,7,10,12,13]. However, all these advantages apply only to the early period after TKR.…”
Section: Discussionmentioning
confidence: 99%
“…Several minimally invasive (MIS) TKR techniques have been described in the literature: mini-midvastus, medial quad-sparing and minisubvastus [1,4,10,12,13]. Many advantages such as faster functional recovery, shorter hospital stay and better early knee range of motion have been reported with different MIS techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Laskin et al [19] reported greater postoperative drainage in the MIS-TKA group than in the standard TKA group. However, Tenholder et al [34] reported that patients with MIS-TKA required fewer transfusions than the patients with the standard approach. Furthermore, the effect of TEA on reducing postoperative bleeding after MIS-TKA has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…O acesso convencional limitado foi desenvolvido para diminuir a morbidade na artroplastia total do joelho e melhorar o pós-operatório imediato, tempo de hospitalização, percentual de transfusão sanguínea e a reabilitação (14)(15) . Essa técnica representa uma transição para a CMI, mas, por utilizar os mesmos parâmetros anatômicos e técnica do procedimento convencional, permitirá que maior número de cirurgiões possa utilizá-la com mais segurança, uma vez que não se propõe que eles mudem radicalmente o que vinha sendo sua prática anterior.…”
Section: Discussionunclassified
“…Recomenda-se que o tamanho da incisão seja a menor possível, mas que deverá estender-se o necessário para permitir visualização adequada dos três compartimentos do joelho e não acarretar sofrimento da pele. Após a incisão da pele, os retalhos cutâneos são mobilizados para que se realize o "conceito das janelas" que permitem visualização adequada da articulação (13)(14)(15) .…”
Section: Acesso Convencional Limitadounclassified